2021
DOI: 10.26508/lsa.202101091
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomics reveals disorder of lipoprotein metabolism in sepsis

Abstract: Sepsis is defined as an organ dysfunction syndrome and it has high mortality worldwide. This study analysed the proteome of serum from patients with sepsis to characterize the pathological mechanism and pathways involved in sepsis. A total of 59 patients with sepsis were enrolled for quantitative proteomic analysis. Weighted gene co-expression network analysis (WGCNA) was performed to construct a co-expression network specific to sepsis. Key regulatory modules that were detected were highly correlated with sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…And these features might serve as biomarker candidates for diagnosis and therapeutic targets. Sixteen proteins, including FIBA, SAA2, A2GL, AACT, CRP, LBP, SAA1, and S10A9, were identified as potential biomarkers in sepsis through integrative multiomics analysis, which is consistent with prior evidence [ 13 ]. These results illustrated that the multiomics analysis results had high reliability.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…And these features might serve as biomarker candidates for diagnosis and therapeutic targets. Sixteen proteins, including FIBA, SAA2, A2GL, AACT, CRP, LBP, SAA1, and S10A9, were identified as potential biomarkers in sepsis through integrative multiomics analysis, which is consistent with prior evidence [ 13 ]. These results illustrated that the multiomics analysis results had high reliability.…”
Section: Discussionsupporting
confidence: 84%
“…Proteomics analysis has been described previously [ 13 ] and used the same biological samples as metabolomics. All proteomic data from the patients with sepsis and NCs analysed in this study were obtained from the ProteomeXchange Consortium ( http://proteomecentral.proteomexchange.org ) via the iProX partner repository with the dataset identifier IPX0003225000.…”
Section: Methodsmentioning
confidence: 99%
“…32 A growing number of studies have concluded that disturbances in substance and energy metabolism are highly relevant to the progression of sepsis. [33][34][35] And cuproptosis is closely linked to the TCA cycle. 36 Therefore, it is reasonable to assume that cuproptosis may play a vital role in the disease progression of sepsis, multi-organ damage and other processes.…”
Section: Discussionmentioning
confidence: 99%
“…showed that TG/cholesterol homeostasis was associated with sepsis-related acute kidney injury [33]. However, many other studies, which involved simple comparisons between survivors and nonsurvivors, reported similar TG levels in deceased patients and survivors [13][14][15][16].…”
Section: Plos Onementioning
confidence: 99%